Discovery of the southernmost locality of Drosera rotundifolia L. in Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
In the article, the discovery of Drosera rotundifolia on the lower Dniper sands in Kherson region (Ukraine) is described with a short description of the species’ southernmost locality in Ukraine.
Keywords: Drosera rotundifolia, lower Dniper sand area, floristic record.